Ultrasound Physics: Innovations in Medical Diagnosis - Nadia Adel Saeed Khaleel al hamdaney; Noor Alhuda Qaed Khalil; Ayman Hussein Qand; Baneen Hussein Kazem Abdullah; Wali Mohammed Ali Aboud (American Journal of Botany and Bioengineering, 2025)
Ultrasound as a non-invasive diagnostic tool has played a primary and significant role in diagnostic radiology since the early 1980s. From that time on, intriguing patient studies and experiments with phantoms were conducted to bridge the gap between basic principles and advanced imaging techniques nowadays performed also in clinical routine. Understanding the relationship of basic physical principles and imaging techniques is important to appreciate the capabilities and limitations of the complex imaging modality. As ultrasound contrasts have had an increasing impact on diagnostic ultrasound imaging in the last decade, they have found special attention. Finally, the progress in the development of new types of contrasts and contrast specific imaging methods is discussed. This overview is intended for a basic understanding of the physics of ultrasound and a survey of current developments and future trends in the field for students and doctors new to medical ultrasound, as well as for researchers in the field. The first application using ultrasound originated from “depth sounding” as conducted on ships in the early 20th century. The measured propagation times of ultrasound provided a measure of the depth of the water. Later, inspection of metals and plastics with ultrasound was used in the construction industry. The great advantage of this NDE method is the non-invasive access to the interior of an object and so it soon became a standard tool for evaluation hardness or particle diameter in different materials. A-B scans were performed in the water-tank inspection of alloy welding seams, which were at least 150 mm thick and welded from both sides. Standard lateral weld seam inspection methods were not sensitive or safe enough. In substations of electric power plants, transformers are oil filled. These oil tanks have to be inspected because there may occur leaks. Because they are situated on an isolating platform, the only way to inspect them was again with ultrasound technology. Now spa machines with infrared stress releasing rays, which were constructed to avoid the occurrence of skin cancer have this effect when operated on the compounds. With the construction of highly sophisticated machines, innovative and unwanted effects were found. On both Triton head parts the warm water flowing through the tubes creates bubbles. The only way to avoid this is regularly to clean the tubes, but this is complicated as you have to switch the tubes.